Determination of the optimal nutrient medium for the cultivation of lactobacteria strains - Абай, Г.Қ.; Чоманов, У.Ч. (Fundamental and Experimental Biology, 2023)
This article presents the results of a study to determine the optimal nutrient medium for the cultivation of lac-tobacteria. The objects of the study were selected pure, active strains of lactic acid microorganisms. In order to determine the optimal nutrient medium of lactobacillus strains, 5 different standard and differentiated nu-trient media were studied – MRS medium, chalk agar, Eikman milk agar, cabbage agar, carrot agar for the cultivation of lactobacteria according to A.I. Netrusov. As a result of studies on carrot agar for the cultivation of lactobacteria according to A.I. Netrusov, the growth of lactic acid bacteria was 3.3 * 107CFU, 3.21*107CFU, 3.05* 10 7CFU, thereby showing a high result. It was revealed that strains of lactic acid bacteria grow well on cabbage agar and MRS medium, the smallest growth was on chalk agar and Eikman milk agar. The peculiarities of the growth of lactobacillus cultures on these media were also investigated, it was revealed that when lactobacillus cultures grow on these media, they form turbidity and enlightenment zones around the colony are observed. These features are related to the composition of the nutrient medium and the physiologi-cal nature of the strain.